2009
DOI: 10.1055/s-0029-1234146
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale and Cryptogenic Stroke: A Matter of Age?

Abstract: A patent foramen ovale (PFO) enables a right-to-left shunt in about a quarter of the population. The marked association between cryptogenic stroke and PFO supports the hypothesis that paradoxical embolism could be a relevant cause of stroke. Although this association has been described in several studies for patients <55 years of age, only limited data are available on the role of PFO in older patients. Recent studies, however, have also shown a significant association between cryptogenic stroke and PFO in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 76 publications
0
26
1
4
Order By: Relevance
“…(27)(28)(29)(30) Although this association with stroke has been more convincingly established in patients younger than 55 years of age, recent studies have also demonstrated significant associations in older patients. (13,28,31,32) In addition, a recent publication illustrated that the co-existence of a PFO with atrial septal aneurysm play an important pathogenic role in the severity of white matter lesions in these patients (odds ratio 2.4; 95% CI: 1.11-5.17) compared to stroke patients without septal abnormalities (p = 0.026).…”
Section: Pfo and Strokementioning
confidence: 99%
“…(27)(28)(29)(30) Although this association with stroke has been more convincingly established in patients younger than 55 years of age, recent studies have also demonstrated significant associations in older patients. (13,28,31,32) In addition, a recent publication illustrated that the co-existence of a PFO with atrial septal aneurysm play an important pathogenic role in the severity of white matter lesions in these patients (odds ratio 2.4; 95% CI: 1.11-5.17) compared to stroke patients without septal abnormalities (p = 0.026).…”
Section: Pfo and Strokementioning
confidence: 99%
“…Transesophageal echocardiography (TEE) is generally considered the reference standard for diagnosis of PFO, using two-dimensional B-mode echocardiography, or color Doppler [10]. A contrast agent, usually saline agitated with air to produce microbubbles is also used, allowing direct visualization of the PFO and atrial septum, and quantification of shunting both at rest and during Valsalva maneuver.…”
Section: Detectionmentioning
confidence: 99%
“…Transthoracic echocardiography may also be used to detect PFO, particularly in conjunction with injected contrast and Valsalva maneuver, but earlier studies reported relative sensitivities for detection of PFO of only 30% to 50%. However, more recent studies with improved technology have reported sensitivities of 90% or more [10,12]. Finally, transcranial Doppler may also be used to detect evidence of right-to-left shunting via a PFO, by detecting the embolic signals of microbubbles in the middle cerebral artery after a contrast injection with or without Valsalva maneuver.…”
Section: Detectionmentioning
confidence: 99%
“…The cause of stroke without identifiable aetiology in PFO patients might be paradoxical thromboembolism [3]. Epidemiologic study has found a significant association between PFO and cryptogenic stroke both in the younger and older patients [3] [4]. It was reported that the incidence of stroke recurrence in PFO patients after medical therapy within a four-year follow-up period was approximately 25% [5].…”
Section: Introductionmentioning
confidence: 99%